Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2018)
A dataset containing 112701 species occurrences available in GBIF matching the query: { "and" : [ "BasisOfRecord is Human Observation", "Geometry POLYGON((-180 20,55 20,55 90,-180 90,-180 20))", "HasCoordinate is true", "TaxonKey is Menyanthes trifoliata L.", "HasGeospatialIssue is false" ] } The dataset includes 112701 records from 217 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0012876-180824113759888/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences